Improvement Of Beginning Reading Literature Skills Through Flash Card Media In Class 1ST A UPsT SPF SDN KIP V Bara-Baraya Makassar City - Nurhaedah Nurhaedah; Siti Raihan; Pratiwi Wulandari (Program Studi PGSD FIP UNM, 2023)
The problem behind this research is the low reading literacy skills of students in grade 1 A UPT SPF SDN KIP V Bara-Baraya Makassar City. This study aims to describe the use of Flash Card media to improve early reading literacy skills of grade 1 A UPT SPF SDN KIP V Bara-Baraya Makassar City students. The research used is classroom action research (CAR) which consists of 2 cycles, each cycle consists of 4 meetings with the stages of activities in the form of planning, implementing, observing, and reflecting. The focus of this research is the use of Flash Card media to improve students' early reading literacy skills. The research subjects were students of class 1 A UPT SPF SDN KIP V Bara-Baraya Makassar City in the even semester of the 2021/2022 academic year, totaling 16 students. Data collection techniques in this study used tests, observations, and documentation. The collection instrument qualitatively used an observation sheet and quantitatively used a preliminary reading skill test. The data analysis technique used is quantitative and qualitative descriptive data analysis. The results showed that there was an increase in early reading literacy skills in the learning process, as evidenced by the class average score of the pre-action was in the sufficient category (C), in the first cycle it increased but was still in the sufficient category (C) while in the second cycle experienced an increase and was in the good category (B). The improvement is based on the process of early reading literacy skills using Flash Card media so that the early reading literacy skills of grade 1 A UPT SPF SDN KIP V Bara-Baraya Makassar City students can increase.